Automotive Companies: Analyst Determinants That Affect Company Value - Dahrani Dahrani (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This study aims to determine the effect of tax planning and return on assets on automotive and component companies listed on the Indonesia Stock Exchange in 2015 – 2020. This research is an associative type of research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained is 7 automotive and component companies listed on the BEI in 2015 - 2020 with a total of 42 observational data for 6 years of observation. The data collection technique used is documentation. The data analysis technique used in this study is multiple linear regression analysis with SPSS 26 software tools. The results of this study indicate that tax planning has no effect on firm value. Return on assets has a positive and significant effect on firm value. Then there is a significant influence between tax planning and return on assets on firm value simultaneously.